Omphalocele and Gastroschisis in Newborns: Over 16 Years of Experience from a Single Clinic - Shunusuke Watanabe; Tatuya Suzuki; Fujio Hara; Toshihiro Yasui; Naoko Uga; Atuki Naoe (EL-Med-Pub, 2017)
Infants born with potentially life-threatening conditions of omphalocele and gastroschisis may require long-term hospitalization. We aimed to compare the outcomes of these two conditions occurring over a 16-year period (2001-16). It is a retrospective study of 19 newborns undergoing surgery for these two abdominal wall defects (8 patients with omphalocele and 11 cases of gastroschisis). The average birth weights for the newborns with omphaloceles and gastroschisis were 2554.5 g and 2248.6 g respectively. Associated anomalies included trisomy 18, Beckwith-Wiedemann syndrome, congenital heart disease, Meckel's diverticulum, inguinal hernias, renal deformities, limb deformities, cryptorchidism, body stalk anomalies, and closed gastroschisis. The average hospital stay for the newborns with omphaloceles and gastroschisis were 42.6 days 50.2 days respectively. The time to the start of postoperative nutritional supplementation for the newborns with omphaloceles and gastroschisis were 4.3 days for the infants with omphaloceles and 7.3 days for respectively. The survival rates for the newborns with omphaloceles and gastroschisis were similar, 87.5% and 81.8% respectively. Survival rates in omphalocele correlated negatively with associated anomalies. In gastroschisis cases, strict care is necessary when intestinal dilation is observed via fetal sonography.